“New Advertisements.” Los Angeles Tri-Weekly News, July 22, 1865, p. 2. Unnamed Ordinance, §§ 1-3, & Unnamed Revised Ordinance, Article 5, § 2. Passed July 17, 1856. Volume 13, Number 12. (Los Angeles) - (:unkn) unknown (General Publisher, 1865)
Prohibited the concealed carry any dirk, pistol, sword-cane, slung-shot, or other dangerous or deadly weapons. Violators fined not more than one hundred dollars and imprisonment at the discretion of the mayor, not exceeding ten days. Also prohibited discharge any pistol, gun, rifle, other description of firearms, or air gun. Violators fined five dollars for the first offense, ten dollars for the second offense, and the third offense not more than fifty dollars, and imprisonment at the discretion of the mayor not exceeding ten days.
--
Keywords: CARRY - CONCEALED